Meningkatkan Pengetahuan Masyarakat Terhadap Digitalisasi Marketing Di Kelurahan Tanggung Kota Blitar - Sita Nadtifatul Ilmi; Al-haq Nauval Susilo Hadi; Farah Daroin Putri Muzakki; Mulik Khabibah; Muhammad Saifuddin Fajari; Verrol Danditya Dhafa Sugiharto; Dewi Puspa Arum (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
This digital era requires people to understand digital in order to increase people's income. The main purpose of socialization is to increase public knowledge of digital marketing to provide the community, especially MSMEs in the Responsibility Village, with the importance of learning new things and using digital as wisely as possible. From the results of the socialization can provide data that can be considered for the future to be able to provide new knowledge to MSMEs in the Respondent Village.